DETEKSI DINI DAN PENCEGAHAN OSTEOPOROSIS PADA LANSIA DI DESA SEI BEROMBANG KECAMATAN PANAI HILIR KABUPATEN LABUHAN BATU TAHUN 2021 - Nurul Rahmah Siregar (Jurnal DIKMAS, 2021)
The purpose of early detection and prevention of Osteoporosis is to increase public understanding of Osteoporosis. The implementation method carried out to carry out community service regarding early detection and prevention of Osteoporosis is to conduct coordination meetings between teams and the Sub-District of Panai Hilir Labuhan Batu, then conducting screenings and by conducting seminars and gymnastics to increase understanding and prevent Osteoporosis in the community, then cross-sectoral cooperation is carried out, then socialization of prevention and early detection of Osteoporosis is carried out, as well as providing assistance and monitoring whether the activities carried out are appropriate to the community or on target